2011
DOI: 10.1007/7854_2011_185
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Genetics of Affective and Anxiety Disorders

Abstract: As shown by clinical genetic studies, affective and anxiety disorders are complex genetic disorders with genetic and environmental factors interactively determining their respective pathomechanism. Advances in molecular genetic techniques including linkage studies, association studies, and genome-wide association studies allow for the detailed dissection of the genetic influence on the development of these disorders. Besides the molecular genetic investigation of categorical entities according to standardized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 313 publications
0
18
0
Order By: Relevance
“…(Samaan et al, 2013) Because the genetics of anxiety and depression are thought to be similar (Domschke and Reif, 2012), it is difficult to explain the harmful effect of FTO on phobic anxiety in our study as compared to the protective effect of FTO on depression reported in the Samaan et al investigation. It is possible that there are differences between ethnic populations as the study of Samaan et al failed to provide a significant effect when analyzing the white population only.…”
Section: Discussionmentioning
confidence: 66%
“…(Samaan et al, 2013) Because the genetics of anxiety and depression are thought to be similar (Domschke and Reif, 2012), it is difficult to explain the harmful effect of FTO on phobic anxiety in our study as compared to the protective effect of FTO on depression reported in the Samaan et al investigation. It is possible that there are differences between ethnic populations as the study of Samaan et al failed to provide a significant effect when analyzing the white population only.…”
Section: Discussionmentioning
confidence: 66%
“…Numerous molecular genetic studies have evaluated the association between polymorphisms in stress-related genes and affective disorders (Domschke and Reif, 2012), but only a few studies have reported an association of variants in these genes with specific drug addictions. We have previously performed association studies of heroin addiction that include several genes related to stress response (Levran et al, 2008; Proudnikov et al, 2008; Levran et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, since previous research has shown that both depression and the brain network metrics are influenced by genes and environment (Bohlken et al 2014;Domschke and Reif 2012;Leonardo and Hen 2006), an additional regression procedure (Begg and Parides 2003;Córdova-Palomera 2015) Values calculated from the number of streamlines (NOS)-weighted matrices SD standard deviation was implemented to determine whether the above mentioned results were driven by the familial or non-genetic factors. Specifically, the previous regression model was tuned using, along with the familial-level covariates gender, age and genotype,…”
Section: Methodsmentioning
confidence: 99%